PHARMACOLOGICAL EVALUATION OF ANTI-INFLAMMATORY, ANALGESIC AND ANTIPYRETIC EFFECTS OF GYNOCARDIA ODORATA ROXB IN ANIMAL MODELS - Rupeshkumar, Mani; Kavitha, Kunchu; Haldar, Pallab Kanti (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Objective: The purpose of this investigation was to study the anti-inflammatory, analgesic, and antipyretic properties of methanol extract of Gynocardia odorata roxb (MEGO) in rats and mice. Methods: The plant material was extracted with methanol. Dose of 200, 400 mg/kg of each extracts were used in carrageenan-induced paw oedema, cotton-pellet granuloma in rats, writhing nociception in mice, and yeast induced hyperpyrexia in rats. Results: All compounds reduced paw oedema into the control group at 5 h post carrageenan injection. The methanol extract of G. odorata roxb were similar to phenylbutazone in reduction of paw oedema and cotton-pellet granuloma. The extract as well as paracetamol induced antinociception in writhing test in comparison to control. Positive results for flavanoids and phenolic compounds were investigated by phytochemical analysis of the extract. The higher antinociception effects of the extract might be due to the presence of flavanoids, and phenol compounds. The methanol extract produced a significant dose dependent inhibition of temperature elevation. Conclusion: These data suggest that the extract of G. odorata roxb produce antinociceptive, anti-inflammatory, and anti-pyretic activities that could be due to the effect of one or a combination of the bio active components in each extract.